2010
DOI: 10.1007/s00359-010-0579-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of testosterone, dihydrotestosterone and estradiol on carotenoid deposition in an avian sexually selected signal

Abstract: Recent studies have demonstrated that carotenoid-based traits are under the control of testosterone (T) by up-regulation of carotenoid carriers (lipoproteins) and/or tissue-specific uptake of carotenoids. T can be converted to dihydrotestosterone (DHT) and estradiol (E2), and variation in conversion rate may partly explain some contradictory findings in the literature. Moreover, most studies on the effect of T on sexual signals have focused on the male sex only, while in many species females show the same sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 80 publications
3
27
0
Order By: Relevance
“…Interestingly, T-females also showed significantly higher values for UV reflectance, represented by PC2. T-induced effects on UV reflectance have been described for plumage and bare-part color in several species [24], [59], [60]. In budgerigars, as shown by the reflectance spectra of untreated males and females measured in this study, reflection in the UV part of the spectrum is normally low in both sexes (see also [61] for an additional spectrum of the male cere).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Interestingly, T-females also showed significantly higher values for UV reflectance, represented by PC2. T-induced effects on UV reflectance have been described for plumage and bare-part color in several species [24], [59], [60]. In budgerigars, as shown by the reflectance spectra of untreated males and females measured in this study, reflection in the UV part of the spectrum is normally low in both sexes (see also [61] for an additional spectrum of the male cere).…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, T-treatment of female zebra finches results in the expression of brighter carotenoid-based red bills, which are still less red than in males [26]. In other species, such as the diamond dove and the moorhen, the extent to which T affects carotenoid-based bare-part colors does not seem to differ between the sexes [24], [25]. As we found that T-females were even less similar to males than C-females for UV reflectance and brightness, our results indicate that in some species the expression of certain aspects of bare-part coloration may also be increased compared to males following T-treatment.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast to astaxanthin, papilioerythrinone was only present in free or monoesterified forms, and never in its diesterified form, as was recently reported for redlegged partridge ornamental traits (Garcia-de Blas et al 2014). Our results support the growing evidence that carotenoid esterification is the rule for living teguments in birds, as well as in fish and reptiles (Pike et al 2011;SanJose et al 2012;Casagrande et al 2011;Garcia-de Blas et al 2013). This contrasts with feather carotenoids, which are deposited in free form or, in some cases, bound to proteins (Mendes-Pinto et al 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Experiment 1 occurred at the beginning of the breeding season, when birds are pairing and testosterone levels are highest in males (Hamner 1966;Duckworth et al 2004), whereas experiment 2 took place during the nestling and post-nesting phase, when house finches become photorefractory and testosterone levels typically drop (Hamner 1968;Duckworth et al 2004). There is a growing body of evidence that testosterone alters carotenoid bioavailability (Blas et al 2006;McGraw et al 2006;Casagrande et al 2011), and experimentally elevated testosterone levels are known inhibit the accumulation of carotenoids in house finch plumage (Stoehr and Hill 2001). Thus, reproductive state and possibly testosterone may influence the accumulation of carotenoids in the retina.…”
Section: Discussionmentioning
confidence: 99%